The Empowerment Strategy Through Spiritual Education (Educare) Toward Gepeng In Denpasar - Srie Kusuma Wardhani, Ni Ketut (Institut Hindu Dharma Negeri Denpasar, 2019)
Gepeng is not only a social pathology or deviant behavior but a case of subculture in the hegemonic, marginalized, and exploitative position. Gepeng is poverty production and poverty is a product of unequal political economic mechanism of the society. This condition has improved the production of empowerment programs. The research showed that Educare is the most strategic empowerment. The scope of problems in this research was about the empowerment strategy of Educare on the alleviation of Gepeng at Denpasar City. The empowerment through the emphasis of spiritual education (Educare) is very potential to transform the personality or and the Gepeng culture. The community adoption program with the Educare philosophy done by the education human value method and applied the three parts, they are education, service (seva), and spiritual. The process of transformation, intellectual emancipation and self-realization is the goal of this empowerment program. The essence of Educare empowerment program is to get the transformation with the social emancipation through self-reflection, positive restructuration (transformation), and to make more access productive capital after Educare program.